2015
DOI: 10.3389/fnins.2015.00279
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of the activity-regulated cytoskeleton-associated protein (Arc/Arg3.1)'s putative role in regulating dendritic plasticity, cognitive processes, and mood in animal models of depression

Abstract: Major depressive disorder (MDD) is primarily conceptualized as a mood disorder but cognitive dysfunction is also prevalent, and may limit the daily function of MDD patients. Current theories on MDD highlight disturbances in dendritic plasticity in its pathophysiology, which could conceivably play a role in the production of both MDD-related mood and cognitive symptoms. This paper attempts to review the accumulated knowledge on the basic biology of the activity-regulated cytoskeleton-associated protein (Arc or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 205 publications
(282 reference statements)
2
56
1
Order By: Relevance
“…Spines are the site of fine-tuning synaptic plasticity, whose induction is much faster than that of large-scale dendritic outgrowth. Activity-regulated cytoskeletal protein (Arc) is a BDNF-regulated immediate early gene has been shown to be instrumental in spine dynamics critical for LTP and learning [60]. We have previously shown that Arc is co-regulated with VGF in hippocampal neurons and that TLQP-62 promotes synaptic plasticity in an acute fashion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Spines are the site of fine-tuning synaptic plasticity, whose induction is much faster than that of large-scale dendritic outgrowth. Activity-regulated cytoskeletal protein (Arc) is a BDNF-regulated immediate early gene has been shown to be instrumental in spine dynamics critical for LTP and learning [60]. We have previously shown that Arc is co-regulated with VGF in hippocampal neurons and that TLQP-62 promotes synaptic plasticity in an acute fashion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Arc expression is induced in a number of brain regions following emotionally-relevant experiences, including exposure to novelty 23,24 , environmental enrichment 25 , and stressful experiences 26,27 . As such, Arc is well positioned to influence mood-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…ARC was demonstrated to be essential for the maintenance of dendritic spine density and morphology (Balu & Coyle, ; Peebles et al, ). AD treatment seems to impact on ARC expression (Li et al, ), likely exerting an effect on neuroplasticity processes.…”
Section: Introductionmentioning
confidence: 99%